Borderline Personality Features in Patients With Persistent Depressive Disorder and Their Effect on CBASP Outcome - Konvalin, Franziska; Grosse-Wentrup, Fabienne; Nenov-Matt, Tabea; Fischer, Kai; Barton, Barbara B.; Goerigk, Stephan; Brakemeier, Eva-Lotta; Musil, Richard; Jobst, Andrea; Padberg, Frank; Reinhard, Matthias A. (Frontiers in Psychiatry, 2021)
Introduction: The Cognitive Behavioral Analysis System of Psychotherapy (CBASP) was developed for the treatment of persistent depressive disorder (PDD), where comorbid personality disorders (PD) are common. In contrast to other PD, comorbid borderline personality disorder (BPD) is often regarded as an exclusion criterion for CBASP. In clinical settings, however, subthreshold BPD symptoms are prevalent in PDD and may not be obvious at an initial assessment prior to therapy. As data on their impact on CBASP outcome are very limited, this naturalistic study investigates BPD features in PDD and their relevance for the therapeutic outcome of a multimodal CBASP inpatient program. Method: Sixty patients (37 female, mean age 38.3, SD 11.9 years) meeting DSM-5 criteria for PDD underwent a 10 weeks CBASP inpatient program. BPD features (i.e., number of fulfilled DSM-5 criteria) together with childhood maltreatment and rejection sensitivity were assessed on admission. Before and after treatment, severity of depressive symptoms was measured using the Montgomery-Asberg Depression Rating Scale (MADRS) and the Beck Depression Inventory (BDI-II). BPD symptoms were assessed using the Borderline Personality Disorder Severity Index (BPDSI-IV) and the Borderline Symptom List (BSL-23). Intercorrelations of baseline characteristics and symptom change during treatment were analyzed. Results: Patients with PDD met a mean of 1.5 (SD 1.6) BPD criteria with 4 patients fulfilling ≥ 5 criteria. BPD symptoms and depressive symptoms showed a strong correlation, and BPD symptoms were additionally correlated with emotional abuse and rejection sensitivity. There was no association between BPD features at baseline and improvement on the MADRS, however, BPD features tended to be associated with a lower response according to the BDI-II score after 10 weeks of treatment. Furthermore, BPD symptoms (i.e., abandonment, impulsivity and affective instability) were reduced after 10 weeks of CBASP treatment. Discussion: BPD symptoms are prevalent in patients with PDD and highly intertwined with the experience of depressive symptoms. In this naturalistic study in PDD, BPD features at baseline did not limit the clinical response to CBASP. Future studies may extend the spectrum of PDD to comorbid subsyndromal or even syndromal BPD in order to develop tailored psychotherapeutic treatment for these complex affective disorders.